Endocrinological abnormalities and Takotsubo cardiomyopathy - George, Anu Anna; John, Kevin John; Selvaraj, Vijairam; Mishra, Ajay Kumar (Monaldi Archives for Chest Disease, 2021)
Dear Editor, We read with much excitement in the article “Takotsubo syndrome and pheochromocytoma: an insidious combination” published by Maffé et al. in your esteemed journal...